The Synthesis of Hybrid Gold-Silicon Nano Particles in a Liquid - Kutrovskaya, S. (Sci Rep, 2017)
We show that the laser ablation method can be efficiently employed for the synthesis of silicon nanoparticles (NP), which are characterized by a strong resonant optical response in the visible spectral range. A single layer composed of silicon NPs has been deposited from the colloidal solution generated by laser ablation. The formation of hybrid silicon-gold NPs as a result of the laser action on a mixed colloidal solution is observed. These hybrid NPs are characterized by broadening of the near-field photoluminescence spectra compared to pure silicon NPs. These results may be used for the realization of functional metasurfaces consisting of randomly distributed resonant NPs.